Oxidation behavior of amorphous boron carbide-silicon carbide nano-multilayer thin films - Bae, K. -E.; Chae, K. -W.; Park, J. -K.; Lee, W. -S.; Baik, Y-J (ELSEVIER SCIENCE SA, 2015)
This experiment studied the effect of nano-multilayer structures of boron carbide film with silicon carbide (SiC) layers on oxidation behavior and hardness. The multilayer films were deposited at 450 degrees C using an unbalanced dual-gun magnetron sputtering system with stoichiometric B4C and SiC targets. The period of the multilayer system (the thickness of one pair of boron carbide and SIC layers) with a constant film thickness was varied between 23 nm and 22.1 nm. The structures of these multilayer thin films were amorphous irrespective of the period. A remarkable hardness enhancement, frequently observed in crystalline nano-multilayer thin film systems, did not appear. The maximum hardness of the multilayer thin film was measured to be about 36 GPa, similar to that of the monolithic boron carbide film deposited under the same condition. Oxidation was, however, greatly reduced by the insertion of the SiC layers. Oxidation was rarely observed at temperatures up to 1200 degrees C, the maximum experimental temperature, whereas significant oxidation was observed at around 700 degrees C in the case of the boron carbide monolithic film. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: BEAM-ASSISTED DEPOSITION; MECHANICAL-PROPERTIES; COATINGS; TEMPERATURES; PROTECTION; HARDNESS